Le paysage rural italien dans les archives d’Emilio Sereni : problèmes et méthodologie pour une recherche - Federico Ferretti (Projets de Paysage)
This paper deals with the archive of Emilio Sereni, recently classified and opened to researchers. We draw here the main lines of a research that will deal with these documents, focusing on the reconstruction of the Sereni’s references about the definition of the idea of landscape, namely in the geographic field. What is the relevance of this corpus for an “archaeology” of the Serenian concept of landscape? What is the role of the Italian and French geographers that he reads, in the construction of his agricultural landscapes? We start here to interrogate his archives.